2017
DOI: 10.1186/s13104-017-2470-7
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of a role of the β4 subunit of the nicotinic acetylcholine receptor in alcohol-related behaviors

Abstract: BackgroundNicotinic acetylcholine receptors have gained attention in the last several years as mediators of alcohol-related behaviors. The genes that code for the α5, α3, and β4 subunits (Chrna5, Chrna3, and Chrnb4, respectively) map adjacent to each other on human chromosome 15/mouse chromosome 9. Genetic variants in this region have been associated with alcohol phenotypes and mice that overexpress these three subunits have reduced ethanol intake. In the present experiments, we examined the role of the Chrnb4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…To determine the nAChRs that underlie varenicline's reduction of ethanol consumption, researchers turned to genetically modified animals. Deletion of the α7, β2, and β4 nAChR subunits did not block the effect of varenicline on ethanol consumption suggesting that these receptor subunits are not involved (Kamens et al, 2010a; Kamens et al, 2017b; Patkar et al, 2016). In contrast, work in genetically modified animals that both increased sensitivity of the α4 subunit and knocked it out demonstrated that this subunit was necessary and sufficient for varenicline-induced reduction of ethanol consumption in adult mice (Hendrickson et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To determine the nAChRs that underlie varenicline's reduction of ethanol consumption, researchers turned to genetically modified animals. Deletion of the α7, β2, and β4 nAChR subunits did not block the effect of varenicline on ethanol consumption suggesting that these receptor subunits are not involved (Kamens et al, 2010a; Kamens et al, 2017b; Patkar et al, 2016). In contrast, work in genetically modified animals that both increased sensitivity of the α4 subunit and knocked it out demonstrated that this subunit was necessary and sufficient for varenicline-induced reduction of ethanol consumption in adult mice (Hendrickson et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…We have previously reported that varenicline increases ethanol-induced sedation in adult mice (Kamens et al, 2010b) and human clinical studies have reported enhanced ratings of alcohol sedation (Fucito et al, 2011). Research in knockout animal models has provided evidence that a number of nicotinic receptor subunits are involved in the sedative effects of ethanol – these include α5, α6, and α7 (Bowers et al, 2005; Kamens et al, 2012; Santos et al, 2013), but not β4 (Kamens et al, 2017b). It is possible that changes in expression and function of nAChRs throughout development (Azam et al, 2007; Doura et al, 2008; Kota et al, 2007) underlie the differences observed between adolescent and adult animals.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to stimulants and opioids, to which adult female rodents are hyper-sensitive (e.g., [6,58,88]), the data pertaining to sex differences in alcohol-induced changes in loco-motor hyperactivity are mixed and vary as a function of species and strain (e.g., [32,53,60,75,76,94]; c.f., [19]). This being said, females tend not to differ from males with respect to behavioral measures of ethanol motor-incoordination and/or intoxication and while the severity of ethanol-induced intoxication varies considerably with strain in mice, the absence of malefemale differences in intoxication is consistent across different mouse strains (e.g., [9,10,24,25,59,75,76,103]).…”
Section: Subject Factor Interactions In the Locomotor Stimulatory Effmentioning
confidence: 93%
“…Finally, in addition to (α4) 3 (β2) 2 , NS9283 potentiates (α2) 3 (β2) 2 and (α2) 3 (β4) 2 nAChRs [18]. Although we cannot exclude the possibility that NS9283 reduced ethanol consumption by acting at these other subtypes, we note that expression of the α2 subunit is low in rodents [41] and studies of β4-null mice suggest that these receptors are not involved in ethanol drinking or intoxication [42,43].…”
Section: Ns9283 Limitationsmentioning
confidence: 68%